Digit Dick and the lost opals - Rees, Leslie, 1905-2000.; Cunningham, Walter (Sydney : John Sands, 1957)
Children's adventure story set in central Australia.
Muir, M. A bibliography of Australian children's books
For children.
Keywords: Race relations - Representation - Literature; Stories and motifs - Animals; Literature and stories - Juvenile